2020
DOI: 10.1051/0004-6361/202039000
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of plasmoids associated with a post-CME current sheet

Abstract: Context. Coronal mass ejections (CMEs) are often observed to be accompanied by flare, current sheets, and plasmoids/plasma blobs. 2D and 3D numerical simulations and observations reported plasmoids moving upward as well as downward along the current sheet. Aims. We aim to investigate the properties of plasmoids observed in the current sheet formed after an X-8.3 flare and followed by a fast CME eruption on September 10, 2017 using extreme-ultraviolet (EUV) and white-light coronagraph images. The main goal is t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…We noticed that our results are consistent with those of Patel et al (2020) who showed that the width of plasmoids can be up to 10 4 km and the area can reach up to 8 × 10 7 km 2 , respectively.…”
Section: Width and Area Distribution Of Plasmoidssupporting
confidence: 93%
See 1 more Smart Citation
“…We noticed that our results are consistent with those of Patel et al (2020) who showed that the width of plasmoids can be up to 10 4 km and the area can reach up to 8 × 10 7 km 2 , respectively.…”
Section: Width and Area Distribution Of Plasmoidssupporting
confidence: 93%
“…Shen et al (2013) investigated the width distribution function of the plasmoids in the CS, and found a power-law distribution in the way of w −2 , with w being the width of plasmoid. Following Clauset et al (2009) that gave the powerlow distribution via the approach of the maximum likelihood, on the other hand, Patel et al (2020) deduced the distribution function of the plasmoid size as f (W ) ∼ w −1.12 .…”
Section: Width and Area Distribution Of Plasmoidsmentioning
confidence: 99%
“…It is only possible when the time interval of recurrent jets is comparable with that of the outflow jets ejected out of the unsolved current sheet (e.g., Cheng et al, 2018). A recent and detailed statistical analysis on the blobs in EUV formed in the post-CME current sheet is given in Patel et al (2020). During magnetic reconnection in solar flares, many observations exhibit that plasmoids are formed in current sheet (Asai et al, 2001;Liu et al, 2009;Takasao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The flares have been observed in the solar atmosphere caused by magnetic reconnection at different spatial scales (Guidoni et al 2016;Benz 2017;Patel et al 2020). These reconnections occurring at various spatiotemporal scales are also considered as one of the mechanisms responsible for the coronal heating.…”
Section: Introductionmentioning
confidence: 99%